Conductive Elastomers with Autonomic Self‐Healing Properties. (25th August 2015) - Guo, Kun; Zhang, Da‐Li; Zhang, Xiao‐Mei; Zhang, Jian; Ding, Li‐Sheng; Li, Bang‐Jing; Zhang, Sheng
Abstract Healable, electrically conductive materials are highly desirable and valuable for the development of various modern electronics. But the preparation of a material combining good mechanical elasticity, functional properties, and intrinsic self‐healing ability remains a great challenge. Here, we design composites by connecting a polymer network and single‐walled carbon nanotubes (SWCNTs) through host–guest interactions. The resulting materials show bulk electrical conductivity, proximity sensitivity, humidity sensitivity and are able to self‐heal without external stimulus under ambient conditions rapidly. Furthermore, they also possess elasticity comparable to commercial rubbers.